2017
DOI: 10.1182/blood-2016-10-747345
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bruton tyrosine kinase with ibrutinib in relapsed/refractory marginal zone lymphoma

Abstract: • Single-agent ibrutinib induced durable remissions (ORR 48%) with a favorable benefit-risk profile in patients with previously treated MZL.• Inhibition of BCR signaling with ibrutinib provides a treatment option without chemotherapy for an MZL population with high unmet need.Marginal zone lymphoma (MZL) is a heterogeneous B-cell malignancy for which no standard treatment exists. MZL is frequently linked to chronic infection, which may induce B-cell receptor (BCR) signaling, resulting in aberrant B-cell surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
200
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(218 citation statements)
references
References 40 publications
11
200
3
4
Order By: Relevance
“…We evaluated the anti‐proliferative activity of the BTK inhibitor, acalabrutinib, and the PI3Kδ inhibitor, ACP‐319, in 11 lymphoma cell lines, derived from ABC‐DLBCL ( n = 4), MCL ( n = 4), and MZL ( n = 3), three subtypes in which BTK inhibition is associated with clinical activity (de Claro et al , ; Wilson et al , ; Noy et al , ). After 72 h of drug exposure, acalabrutinib showed a potent anti‐proliferative activity in ABC DLBCL TMD8 and OCI‐LY‐10 (50% inhibitory concentration [IC50] 7 nmol/l and 1·5 nmol/l respectively), whereas the activity was modest in VL51 (IC50 3·2 µmol/l) and in all other cell lines (IC50s >10 µmol/l).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the anti‐proliferative activity of the BTK inhibitor, acalabrutinib, and the PI3Kδ inhibitor, ACP‐319, in 11 lymphoma cell lines, derived from ABC‐DLBCL ( n = 4), MCL ( n = 4), and MZL ( n = 3), three subtypes in which BTK inhibition is associated with clinical activity (de Claro et al , ; Wilson et al , ; Noy et al , ). After 72 h of drug exposure, acalabrutinib showed a potent anti‐proliferative activity in ABC DLBCL TMD8 and OCI‐LY‐10 (50% inhibitory concentration [IC50] 7 nmol/l and 1·5 nmol/l respectively), whereas the activity was modest in VL51 (IC50 3·2 µmol/l) and in all other cell lines (IC50s >10 µmol/l).…”
Section: Resultsmentioning
confidence: 99%
“…MZL is also associated with chronic inflammation, leading to continuous B cell stimulation by BCR signaling. A phase 2 trial for single-agent ibrutinib in patients with relapsed/refractory MZL showed high efficacy by disrupting the BCR signaling with ibrutinib [36]. Patients with at least one prior anti-CD20-based therapy showed ORR of 51% with median duration of response of 19 months.…”
Section: Btk Inhibitor Ibrutinibmentioning
confidence: 99%
“…Treatment with ibrutinib (PCI-32765) has been shown to induce considerable efficacy to patients with untreated and relapsed/refractory CLL, ABC-DLBCL, FL, MCL, marginal zone lymphoma, and lymphoplasmacytic lymphoma. 9093 However, ibrutinib may have certain limitations. First, some lymphomas do not just depend on the BCR and NF-κB pathways but may depend on other BTK-independent pathways or genetic mutations; therefore, these lymphomas may show constitutive resistance to ibrutinib.…”
Section: Therapeutic Biomarkers Related To Oncogenic Pathways Inmentioning
confidence: 99%